ANALISIS HALAL SUPPLY CHAIN MANAGEMENT AYAM BROILER DI KOTA AMBON - Latuconsina, Nahriah (IAIN Ambon, 2024)
This study aims to find out how the halal supply chain management process for broiler chickens in Ambon City and the role of BPJPH in supervising selected distributors of broiler chickens with a halal label in Ambon City. This research type is field research with a descriptive qualitative method. The research subjects were BPJPH or the Maluku Province Halal Certification Service Task Force and Broiler Chicken Distributors. The research focuses on the Supervision of halal products from BPJPH or the Provincial Halal Certification Service Task Force. While the techniques used were observation, interviews, and documentation. The results showed that the implementation of halal supply chain management in the mardika market did not work as it should, due to the transfer of duties and functions of the Indonesian Ulema Council (MUI) to the Organizing Body for Halal Product Guarantee (BPJPH). so almost all broiler chicken sellers do not know the function of BPJPH and do not know and have met with supervision from BPJPH or the Maluku Province Halal Certification Service Task Force. Lack of supervision from the Provincial Halal Product Assurance Service Task Force both at distributors and at retailers or small business actors in the mardika market in Ambon city. In addition to the Provincial Halal Certification Service Task Force, statements from several consumers that the products consumed must be halal because what is evident from their eyes is the appearance of the seller and the cleanliness of the sales process and do not pay much attention to the existence of a form of halal guarantee in the form of a halal logo on the product. sales process and do not pay much attention to the existence of a form of halal guarantee in the form of a halal logo on the product.. Keyword: halal supply chain management, BPJP